Comparing Prospectively Recorded Posttraumatic Amnesia Duration With Retrospective Accounts. Issue 2 (March 2016) - Roberts, Caroline M.; Spitz, Gershon; Ponsford, Jennie L.
Abstract : Objective: Limited research has been conducted comparing different methods for determining the duration of posttraumatic amnesia (PTA). This study compared prospectively recorded PTA duration (P-PTA) with retrospective reports of the return of continuous memory (R-PTA). Participants: Fifty-nine individuals admitted to a head injury rehabilitation unit with a traumatic brain injury who had their PTA duration recorded using the Westmead Post-Traumatic Amnesia Scale. Participants were between 6 months and 6 years postinjury at the time of study. Measures: P-PTA was determined on the basis of Westmead Post-Traumatic Amnesia Scale responses. R-PTA was ascertained using a semistructured telephone interview. Results: Although the PTA measures were significantly positively correlated ( r = 0.76), mean R-PTA was significantly longer than mean P-PTA. In 34 cases (57.6%), R-PTA was longer than P-PTA (13 participants moved to a higher injury severity band), and in 22 cases (37.3%), R-PTA was shorter than P-PTA (8 participants moved to a lower injury severity band). The difference between P-PTA and R-PTA was not significantly associated with age, Glasgow Coma Scale score, overall PTA duration, or the number of days postinjury of the retrospective interview. Conclusions: Prospective and retrospective estimates of PTA duration were not comparable within the present sample. Further research comparing the two methods is needed.